Impact of Accelerated Thermal Aging on Electrical Tree Structure and Physicochemical Characteristics of XLPE Insulation - Sahoo, Rakesh; Karmakar, Subrata (IEEE transactions on dielectrics and electrical insulation, 2024)
Cross-linked polyethylene (XLPE) insulation undergoes thermal aging due to load or environmental stresses over its service life. The aging process causes the XLPE to deteriorate, leading to the production of chemical byproducts that results in insulation defect. In this study, the impact of thermal aging in terms of the electrical and physicochemical characteristics of XLPE insulation is emphasized. In order to accelerate the aging process, 33 kV high voltage XLPE cable samples are heated for 120 and 240 hours at 150°C, compared to an unaged sample. Due to thermal aging micro-voids, cracks are formed and the crystallization of polymeric material deteriorates, which affects the electrical tree growth characteristics. Also, during the aging formation of carbonyl index, molecular change, degree of crystallinity, enthalpy of fusion, and nature of hydrophobicity is observed by Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), X-ray diffraction (XRD), Differential scanning calorimetry (DSC), and Contact angle measurement respectively. The results show that the microstructure of the unaged sample is more resistant to thermal and oxidative stress than that of the aged sample. The molecular structure of the sample breaks down due to the thermo-oxidation reaction, and the crystal area is damaged as a result of long-term use, which decreases insulation performance.